Pauzy v trenirovochnom protsesse u zhenshchin-sportsmenok, vyzvannye beremennostyu, i ikh vliyanie na sportivnye distizhenya - Vovk, S. I. (Teorija i Praktika fiziceskoj Kul'tury, 2002)
One of the basic biological functions of women - child-birth - imposes the certain restrictions on training of women during pregnancy. Female athletes during pregnancy and some time after it weaken training loads or interrupt the training process. Questions of these breaks influence on achievements in sport of female athletes are urgent in this connection. The literary data, the results of questioning and interviewing were used at the realization of the research. The logic-statistical analysis of the received data was carried out. The tactics of women's behavior during pregnancy and after it is very individual as results of the research have been shown. The duration of breaks in the basic sports training can be various on many factors - household, social, individual morphofunctional, mental, medical.